Psikoedukasi Pencegahan Adiksi Pornografi Bagi Anak dan Remaja - Rahayu, Puspita Puji (Universitas Pahlawan Tuanku Tambusai, 2024)
The increasing cases of pornography addiction in children and adolescents have become a serious problem that threatens mental health and social development. Thus, psychoeducation is very important. The negative impacts that arise are brain and physical damage that will be damaged gradually. This community service activity aims to help prevent and handle the dangers of pornography addiction through psychoeducation. Psychoeducation is one of the interventions that can be given to students for children and adolescents so that they are not exposed to and do not access pornographic videos, or at least can reduce the level of addiction for children and adolescents who are already addicted to pornography. sychoeducation in this case will be carried out through methods of target audience identification, needs analysis, development of psychoeducational materials, program implementation, and evaluation. This psychoeducation will be conducted for children and adolescents in Bugangan Sub Disctrict, Semarang City. The results of this community service activity show a significant success in increasing understanding and awareness about the dangers of pornography addiction among children and adolescents.